2021
DOI: 10.1111/all.14991
|View full text |Cite
|
Sign up to set email alerts
|

One Health: EAACI Position Paper on coronaviruses at the human‐animal interface, with a specific focus on comparative and zoonotic aspects of SARS‐CoV‐2

Abstract: The latest outbreak of a coronavirus disease in 2019 (COVID‐19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), evolved into a worldwide pandemic with massive effects on health, quality of life, and economy. Given the short period of time since the outbreak, there are several knowledge gaps on the comparative and zoonotic aspects of this new virus. Within the One Health concept, the current EAACI position paper dwells into the current knowledge on SARS‐CoV‐2’s receptors, symptoms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 219 publications
(573 reference statements)
0
17
0
Order By: Relevance
“…7 maropitant 1 mg/kg q24h IV for treatment of gastrointestinal signs, such as vomiting and anorexia. 8 mirtazapine ointment q24h for appetite stimulation. 9 silymarin 20 mg/kg q12h PO for 10 days and then 20 mg/kg q24h PO for treatment of increased liver enzymes.…”
Section: In Vivo Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…7 maropitant 1 mg/kg q24h IV for treatment of gastrointestinal signs, such as vomiting and anorexia. 8 mirtazapine ointment q24h for appetite stimulation. 9 silymarin 20 mg/kg q12h PO for 10 days and then 20 mg/kg q24h PO for treatment of increased liver enzymes.…”
Section: In Vivo Study Designmentioning
confidence: 99%
“…Their high diversity causes the continuous emergence of new coronavirus variants that can have changed target cell tropism and/or host spectrum and lead to interspecies or zoonotic transmission; recent examples of the latter are Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and the most recent Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) causing Coronavirus Infectious Disease 2019 (COVID-19) [4][5][6][7]. The newly emerging coronavirusassociated diseases raise awareness of the potential risks of highly virulent coronavirus infections in humans with close contact to animals harboring coronaviruses [8]. Shifts in tissue or cell tropism resulting in changes in virulence are distinctive features of coronaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 is spread almost exclusively through human–human transmission, experimental studies have demonstrated human–animal and animal–animal transmission of SARS-CoV-2, the causative agent of COVID-19, in several species, such as cats, farmed mink, and non-human primates [ 8 , 9 ]. Considering the global popularity of pet ownership, including 57% of US households [ 10 ], the possible transmission of SARS-CoV-2 between humans and companion animals is particularly concerning.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from anaphylaxis on first injection, which presupposes pre-existing sensitization [ 24 ], no statement can currently be made as to whether the first partial vaccination per se can lead to specific sensitization. A total of only four cases of anaphylactic reaction after the second administration have been documented [ 13 ].…”
Section: Discussionmentioning
confidence: 99%